2013
DOI: 10.1002/jcc.23474
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule‐mediated control of hydroxyapatite growth: Free energy calculations benchmarked to density functional theory

Abstract: The unique, plate-like morphology of hydroxyapatite (HAP) nanocrystals in bone lends to the hierarchical structure and functions of bone. Proteins enriched in phosphoserine (Ser-OPO3) and glutamic acid (Glu) residues have been proposed to regulate crystal morphology; however, the atomic-level mechanisms remain unclear. Previous molecular dynamics studies addressing biomineralization have used force fields with limited benchmarking, especially at the water/mineral interface, and often limited sampling for the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
103
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(118 citation statements)
references
References 73 publications
14
103
1
Order By: Relevance
“…On the other hand, we previously found that plate-like CaP formed in the confined gap region without intermediate spherical ACP 23 . Similar 2D crystallization can occur by the preferential adsorption of small acidic molecules, such as phosphoserine and citrate, on specific faces of apatite nuclei 38 , 39 . To quantitatively evaluate nucleation in the confined gap region (IM), we developed a model of nucleation in which 2D crystals grow only in the lateral directions with a uniform height (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…On the other hand, we previously found that plate-like CaP formed in the confined gap region without intermediate spherical ACP 23 . Similar 2D crystallization can occur by the preferential adsorption of small acidic molecules, such as phosphoserine and citrate, on specific faces of apatite nuclei 38 , 39 . To quantitatively evaluate nucleation in the confined gap region (IM), we developed a model of nucleation in which 2D crystals grow only in the lateral directions with a uniform height (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…The precise role of each of the peptide structures remains unclear. However, as MD is sensitive to initial conditions, we will compare these preliminary MD data with experimental in vitro results to refine the initial conditions before applying others sophisticated computational techniques (9). …”
Section: Discussionmentioning
confidence: 99%
“…A HAP slab with dimensions of 37.7 Å×34.4 Å×32.3 Å is created as the HAP (100) model surface. The detailed procedure for building the HAP (100) surface can be found elsewhere . Due to the high charge density distribution, the HAP (100) face, as a hydrophilic surface, exhibits strong binding affinity with amino acids and peptides .…”
Section: Models and Calculation Protocolsmentioning
confidence: 99%
“…The detailed procedure for building the HAP (100) surface can be found elsewhere . Due to the high charge density distribution, the HAP (100) face, as a hydrophilic surface, exhibits strong binding affinity with amino acids and peptides . For the HAP surface model, we have not considered hydroxylation and protonation of surface ions, which could cause the formation of monohydrogen phosphate/dihydrogen phosphate and removal of a stoichiometric amount of calcium ions.…”
Section: Models and Calculation Protocolsmentioning
confidence: 99%
See 1 more Smart Citation